Investigating process skills and competency gaps in undergraduate agricultural extension curriculum in selected South African universities - Niekerk, J.A. van; Maltitz, L. von; Davis, Kristin E. (Academy of Science of South Africa, 2022)
The Michigan State University Alliance for African Partnership (AAP) launched a multi-country study to contribute to upgrading and tailoring the agricultural extension curricula at participating institutions. The first phase of primary data collection consisted of focus group discussions. The focus groups were structured around a specific objective: gathering information around specific questions. Focus group discussions were followed by an online survey of Agricultural Extension and Advisory Services (AEAS) role players, of which the results will be discussed separately. It was concluded from the focus group discussions that the AEAS workers in South Africa lacked the critical skills to perform their responsibilities efficiently. Several required skills were singled out during the focus group discussions. It was concluded that it is vital for agricultural development in the country to ensure that these skills and competencies are included in all South African teaching institutions' curricula. It is therefore recommended that it is critical for each institution offering agricultural extension training to keep the curriculum relevant so that it meets the needs of the profession. Keeping the curriculum relevant includes participatory curriculum development (PCD), regular review of the curriculum by all the stakeholders of the profession, and the necessary collaborations with professional bodies to regulate the curriculum. The efficiency in the sector will be enhanced if AEAS qualifications at the various training institutions cater to the profession's demands.